Variasi Vokal Bahasa Melayu di Riau Daratan dan Riau Kepulauan - Hidayatul Astar (Kantor Bahasa Provinsi Maluku Utara, 2013)
This article is a study of vowel variation of Malay language in the land of Riau and the Islands of Riau. This is a comparative study which aims to compare given vowels in ane tymon on the first and the second syllable of Malay language in two regions. The results show that Malay vowels in the Island of Riau are more varied than in the Land of Riau: 63% on the second syllable; 37% on the first syllable. Vocals on the second syllable of the islands of Riau and the land of Riau are more than the first vocals. Vocals on the first syllable are [a],[Ù], [u], [o], and [i], while the second syllables are [a]; [o], [e]; [Ù], [], [iya], [i], [u],and [uwa]. as Riau islands has more vocal variations, this region is considered as the center of vocal innovation.